Exhausted on the cross - Darwīš, Naǧwān 1978- (New York Review Books poets, 2021)
"From a foremost contemporary Arab poet comes a book of deep poetic sensitivity, power, wit, and existential self-questioning. In a second major book to have been translated into English by Kareem James Abu-Zeid, following the critically acclaimed Nothing More to Lose, the Palestinian poet Najwan Darwish takes the reader on a dizzying journey across histories, cultures, and geographies. With Haifa and Jerusalem as its anchoring points, Exhausted on the Cross takes us from the grime of modern-day Shatila to the opulence of medieval Baghdad, from the gardens of Samarkand to the open-air prison that is Gaza. We join the Persian poet Hafez in the conquered city of Shiraz, and we converse with the Prophet Mohammad in Medina. In this eagerly awaited book from a poet with broad international appeal the universal themes of death, creation, human struggle, oppression, and tragedy come into sharp and intensely personal focus"--